(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
In this article, the role of healthy lifestyle in society is incomparable. There are priority tasks such as forming a healthy way of life, raising a highly moral and well-rounded person who has an independent mind and lives with a purpose.